A Comparative Study for The Alcoholic Extract Effect of Ajwa Dates (Phoenix Dactylifera L) in Protection of the Hepatic and Renal Tissues from Toxicity Induced by Aspergillus Niger in Albino Rats - Alaa Abdul Ali Al-Khafaf (Journal of Global Pharma Technology, 2017)
The plant extracts and their chemical components have a long history as antifungal agents to control the growth of isolations that released toxins and for this reason, they were used in the bio techniques as a preservative due to increased fungal resistance to the fungal antibiotics. The study aimed to evaluate the efficiency of the alcoholic and aqueous extracts for Ajwa dates in inhibiting the production of Ochratoxin A from Aspergillus Niger, and study the possible protective effect of these extracts on the tissues of vital organs such as liver and kidneys against the toxicity that induced by Ochratoxin A. The analysis results of the chromatography methods (HPLC, TLC) showed an influence of these two extracts on the production of Ochratoxin A, and the full inhibitory impact for the production of this type of fungal toxin was in the two concentrations ( 25, 20 mg / mL) by using the medium of Yeast Extract Sucrose (YES). The present study did not find any significant differences (P˃0.05) between the activity of aqueous and alcoholic extract in Ochratoxin A inhibition. The present study performed in the animal house of Biology department/Faculty of Education for Girls, twenty laboratory male rats of Sprague-Dawley strain were divided into four equal groups, the first group of animals (control) was orally administrated with normal saline solution (0,9%),the second group was orally given alcoholic extract of Ajwa dates at the concentration of (1) mg/kg, while the third group was orally treated with Ochratoxin A at the concentration of (289) μg /kg ,with regard to the last group was orally received alcoholic extract of Ajwa dates (1) mg/kg + Ochratoxin A (289) μg /kg respectively, the treatment of all animals was once daily for five days a week. During this study the body weight as well as the relative weights of liver and kidneys for rats were recorded, also the effectiveness of some hepatic enzymes (Aspartate amino transferase AST, Alanine amino transferase ALT and Alkaline phosphatase ALP) was estimated, in addition to the other biochemical parameters such as urea and creatinine levels, also the study was comprised the preparation of histological sections for liver and kidneys. The statistical analysis results of the current study were revealed ,Ochratoxin A caused a significant decrease (P˂0.05) in the body weight at the group of rats that treated with it when compared with the other experimental groups ,contrary to that, the Ochratoxin A showed a significant increase (P˂0.05) in the relative weights of liver and kidneys ,effectiveness of hepatic enzymes AST,ALT , ALP, levels of urea and creatinine at the male rats were submitted to this type of mycotoxin compared to the other groups of study. In relation with the microscopic examination of liver and kidney sections for the laboratory animals that treated with Ochratoxin A, several patho-histological changes were noted as compared with the other groups. From the results of this study can be concluded that the alcoholic extract of Ajwa dates was ameliorated the functional performance of both liver and kidneys through its preservative properties to protect the tissues of those organs from the nephrotoxicity and hepatotoxicity that induced by Ochratoxin A. Keywords: Ochratoxin A, Ajwa dates, Patho-histological effects, Biochemical properties